The Role of Women in Improving Family Welfare through Family Planning Safari Program: The Role of Women in Improving Family Welfare through Family Planning Safari Program - Septiana Juwita; Niken Bayu Argaheni; Asih Sri Marni; Mida Hutajulu (UNUSA Press, 2023)
Background: Women are one of the supports for national development that is not only seen from the social sphere. The success of the family planning program is highly dependent on community participation, namely family commitment between mothers and husbands. The participation and empowerment of women in contributing to the success of the family planning program is a potential strategy for increasing women's access and cultural transformation. Community service aims to increase women's knowledge and understanding of their role in improving family welfare through family planning safaris. Methods: Health counselling was used as a way to improve community health. A pretest and posttest related to the theme were conducted to determine the results of the improvement and understanding of participants. Results: There was an increase in knowledge and understanding from the pretest results showing that only 71% of women knew and understood the role of women. After receiving health counselling, women's knowledge and understanding became 100%. Conclusion: This means that counselling is still an effective way to empower by increasing knowledge and understanding related to the role of women as a way to improve family welfare through the Safari KB program.